TAZKIYATUN NAFS IN CLASSICAL AND MODERN ISLAMIC TRADITION Qur’anic Worldvie - Belinda Dwijayanti (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2015)
This study aims to discover the interpretation of tazkkiyatun nafs according to classical islamic scholar; al-Alusi and modern one; Hamka. Whereas the method is library based-research and the collected data is gained by employing two keywords; al-nafs and tazkiyatun nafs. This research is also called as comparative study between classical islamic scholar; al-Alusi and modern one; Hamka, because of the analysis which uses comparative method to draw an inference between Hamka’s thought in al-Azar and al-Alusi’s in Ruh al Ma’ani. The acquired result is that soul purification according to classical islamic scholar; al-Alusi and modern one; Hamka which is purifying soul from atheist, polytheism, and wickedness act. The reward from soul purification is a calm soul and happiness in this world and hereafter.